Composition of artisanal fishing landings in the ports of Boca Parita and Agallito, Panamanian Pacific - Vergara-Frías, Yarkelia Aneth (2021)
For the ports of Boca de Parita and El Agallito, in the Panamanian Pacific, biomass landed was counted for the period between 2011 and 2015. The individuals in these landings were also identified, measured and weighed, and the prices paid by intermediaries to fishermen were recorded. The results of these efforts indicate that a total of 2.8 tons of fishery products from both ports were marketed, with 74.5% of the total landed at Boca Parita and the remainder at El Agallito. In the landings, 38 species were identified, of which the most abundant: Cynoscion phoxocephalus (Scianidae), Scomberomorus sierra (Scombridae) and Lutjanus guttatus (Lutjanidae). For both ports, over 90% of landings consisted or first and second quality products in terms of market price. Size distributions for species with a sample size of more than 100 individuals for which data on mean reproductive size (L50) was also available indicate that in the cases of Caranx vinctus and Centropomus medius, over 80% of landings consisted of mature individuals, while for Lutjanus guttatus and Scomberomorus sierra 49% and 53%, respectively, of individuals were mature. The percentages of mature individuals of Cynoscion phoxocephalus, Caranx caballus and Cynoscion albus were 19, 5 and 0%, respectively. This indicates a need to establish management policies which regulate catch size and/or establish no-take zones that guarantee the capture of individuals that have already reproduced, as a first step in ensuring the sustainability of artisanal fishery in the Parita Gulf.